Results of the standard set for pulmonary sarcoidosis: feasibility and multicentre outcomes - Kampstra, Nynke A. (ERJ Open Res, 2019)
Our study presents findings on a previously developed standard set of clinical outcome data for pulmonary sarcoidosis patients. We aimed to assess whether changes in outcome varied between the different centres and to evaluate the feasibility of collecting the standard set retrospectively. This retrospective observational comparative benchmark study included six interstitial lung disease expert centres based in the Netherlands, Belgium, the UK and the USA. The standard set of outcome measures included 1) mortality, 2) changes in pulmonary function (forced vital capacity (FVC), forced expiratory volume in 1 s, diffusing capacity of the lung for carbon monoxide), 3) soluble interleukin-2 receptor (sIL-2R) change, 4) weight changes, 5) quality-of-life (QoL) measures, 6) osteoporosis and 7) clinical outcome status (COS). Data collection was considered feasible if the data were collected in ≥80% of all patients. 509 patients were included in the retrospective cohort. In total six patients died, with a mean survival of 38±23.4 months after the diagnosis. Centres varied in mean baseline FVC, ranging from 110 (95% CI 92–124)% predicted to 99 (95% CI 97–123)% pred. Mean baseline body mass index (BMI) of patients in the different centres varied between 27 (95% CI 23.6–29.4) kg·m(−2) and 31.8 (95% CI 28.1–35.6) kg·m(−2). 310 (60.9%) patients were still on systemic therapy 2 years after the diagnosis. It was feasible to measure mortality, changes in pulmonary function, weight changes and COS. It is not (yet) feasible to retrospectively collect sIL-2R, osteoporosis and QoL data internationally. This study shows that data collection for the standard set of outcome measures for pulmonary sarcoidosis was feasible for four out of seven outcome measures. Trends in pulmonary function and BMI were similar for different hospitals when comparing different practices.